A specific SNP-based multiplex PCR assay for the simultaneous identification of two biological ingredients for the Chinese patent medicine, Danggui Buxue pill - Liu, Yinrong; Yang, Yingying; Zhou, Zishan; Fan, Jia’er; Diao, Jianxin; Chao, Zhi; Tian, Enwei (Frontiers in Pharmacology, 2023)
Background: An increasing number of Chinese patent medicines (CPM) have been widely used in East Asian and North American countries, and the safety and efficacy of CPM have highly attracted public attention. However, it is difficult to supervise the authenticity of multiple biological ingredients within CPM based on microscopic inspection and physical and chemical detection. The raw materials may have similar characteristics of tissue structures and ergastic substances or similar chemical composition and contents when substitutes and/or adulterants are added. DNA molecular markers have been used to distinguish the biological ingredients within CPM based on conventional PCR assay. However, it was proved to be time- and labor-consuming and reagent-wasting, as multiple PCR amplification strategies were required for identifying the complex species composition within CPM. Here, we took the CPM (Danggui Buxue pill) as an example and aimed to establish a specific SNP-based multiplex PCR assay and simultaneously determine the authenticity of the two biological ingredients (Angelicae Sinensis Radix and Astragali Radix) within this CPM. Methods: We, respectively, designed the species-specific primers based on highly variable nrITS for discriminating Angelicae Sinensis Radix and Astragali Radix from their common substitutes and adulterants. The specificity of the primers was checked through conventional PCR assay and multiplex PCR assay. Furthermore, we used a handcrafted Danggui Buxue pill sample (DGBXP) to optimize annealing temperatures for the primers with multiplex PCR, and the sensitivity was also assessed. Finally, fourteen batches of commercial Danggui Buxue pills were used to verify the stability and practicability of the established multiplex PCR assay. Results: Two pairs of highly species-specific primers for amplifying Angelicae Sinensis Radix and Astragali Radix were screened, and our established multiplex PCR assay showed high specificity and sensitivity (lowest detection concentration: 4.0 × 10−3 ng/μL) at an optimal annealing temperature of 65°C. The method could simultaneously identify both biological ingredients within the Danggui Buxue pill. Conclusion: The specific SNP-based multiplex PCR provided a simple, time-, and labor-saving method for the simultaneous identification of the two biological ingredients within Danggui Buxue pills. This study was expected to provide a novel qualitative quality control strategy for CPM.